1975
DOI: 10.2140/pjm.1975.60.95
|View full text |Cite
|
Sign up to set email alerts
|

Generalized right alternative rings

Abstract: Introduction. We shall call a ring a GRA ring (for generalized right alternative ring) if it satisfies the following three identities:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A simple 2-torsion free right alternative algebra is either alternative, hence associative or Cayley algebra over its center. Also in 1975, the work of Hentzel [83] was dealt with a GRA (generalized right alternative) ring R. It was shown that I is an ideal of R, that I is commutative, and that I is the sum of ideals of R whose cube is zero. This means that if R is simple, or even nil-semisimple, and then R is right alternative.…”
Section: Alternative Rings (1930-2015)mentioning
confidence: 99%
“…A simple 2-torsion free right alternative algebra is either alternative, hence associative or Cayley algebra over its center. Also in 1975, the work of Hentzel [83] was dealt with a GRA (generalized right alternative) ring R. It was shown that I is an ideal of R, that I is commutative, and that I is the sum of ideals of R whose cube is zero. This means that if R is simple, or even nil-semisimple, and then R is right alternative.…”
Section: Alternative Rings (1930-2015)mentioning
confidence: 99%